Systematic review of obstetric care from a women‐centered perspective in Nigeria since 2000. Issue 1 (3rd November 2016) - Hirose, Atsumi; Owolabi, Oluwatoyin; Imamura, Mari; Okonofua, Friday; Hussein, Julia
Abstract: Background: A women‐centered approach can improve the quality of patient care. Objective: To review issues in the provision of obstetric care from a patient‐centered care perspective in Nigeria. Search strategy: Using terms related to maternal and perinatal mortality, in combination with "Nigeria", MEDLINE, Embase, CINAHL, Web of Knowledge, and African Journal Online were searched, between December 1, 2013 and January 31, 2014, for articles in any language. Selection criteria: Articles published in a Nigerian setting after 2000 that investigated causes of and circumstance surrounding maternal deaths and complications, or clinical practice related to maternal care were included. Data collection and analysis: Data were extracted by two reviewers using a standardized abstraction form and were analyzed from a patient‐centered perspective. Main results: The analysis included 57 studies. Clandestine induced abortions, lack of prenatal care, delays in seeking care, and the use of spiritual churches for delivery were found to contribute to adverse pregnancy outcomes. Conclusions: Healthcare systems respond inadequately to patients' needs in terms of abortion care, information sharing, transitioning between prenatal and obstetric care, and patients' non‐medical needs. Data from clinician‐led maternal death audits provided insights into how women‐centered care can be provided; nonetheless, more‐focused studies from a primarily patient‐centered perspective are warranted. Abstract : Data from clinician‐led maternal death audits provided insight into current gaps in the provision of patient‐centered maternal healthcare in Nigeria.